Cap d'Encre. - Cap d'Encre, Bruxelles (Bruxelles : Cap d'Encre, 1966)
Belgeonne, Gabriel ; Carcan, René ; De Bolle, Francis ; Laffineur, Marc ; Lismonde ; Marchoul, Gustave ; Dragulj, Emir
Groupe sept graveurs belges
boek